2009
DOI: 10.1007/s00384-009-0703-5
|View full text |Cite
|
Sign up to set email alerts
|

Fast-track vs standard care in colorectal surgery: a meta-analysis update

Abstract: FT protocols show high-level evidence on reducing primary and total hospital stay without compromising patients' safety offering lower morbidity and the same readmission rates. Enhanced recovery programs should become a mainstay of elective colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
184
2
16

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(209 citation statements)
references
References 37 publications
7
184
2
16
Order By: Relevance
“…Although growing evidence from several RCTs, systematic reviews and meta-analyses suggest significant benefits from ERAS pathways, there are still major difficulties when introducing these evidence-based guidelines into routine practice. 9,84,87 The fact that less than half of patients are involved in a postoperative care pathway suggests that perioperative care continues to resemble traditional and conventional attitudes. 88,89 Many surgeons state that they have "never heard of ERAS," while others cite inadequate multidisciplinary and community support as an impediment to implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Although growing evidence from several RCTs, systematic reviews and meta-analyses suggest significant benefits from ERAS pathways, there are still major difficulties when introducing these evidence-based guidelines into routine practice. 9,84,87 The fact that less than half of patients are involved in a postoperative care pathway suggests that perioperative care continues to resemble traditional and conventional attitudes. 88,89 Many surgeons state that they have "never heard of ERAS," while others cite inadequate multidisciplinary and community support as an impediment to implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Randomised studies showed a reduction in hospital days without compromising the safety of the patients, with a lower morbidity and a readmission rate similar to the one of colonic surgery with conventional care [14].…”
Section: Introductionmentioning
confidence: 89%
“…Studies of fast track general surgery rarely include cost analyses 2,16,17 . Clinical outcomes speak in favor of cost-effectiveness even though no analyses have previously been presented.…”
Section: Commentmentioning
confidence: 99%